The Roll in England and France in the Late Middle Ages - Holtz, Stefan G.; Peltzer, Jörg; Shirota, Maree (Materiale Textkulturen, 2020)
In the Middle Ages, rolls were ubiquitous as a writing support. While scholars have long examined the texts and images on rolls, they have rarely taken the manuscripts themselves into account. This volume readdresses this imbalance by focusing on the materiality and various usages of rolls in late medieval England and France. Researchers from England, France, Germany and Singapore demonstrate in 11 contributions how this approach can increase our understanding of the rolls and their contents, as well as the contexts in which they were produced and used.